Gap junctions and hemichannels composed of connexins: potential therapeutic targets for neurodegenerative diseases - Takeuchi, Hideyuki; Suzumura, Akio (Frontiers in Cellular Neuroscience, 2014)
Microglia are macrophage-like resident immune cells that contribute to the maintenance of homeostasis in the central nervous system (CNS). Abnormal activation of microglia can cause damage in the CNS, and accumulation of activated microglia is a characteristic pathological observation in neurologic conditions such as trauma, stroke, inflammation, epilepsy, and neurodegenerative diseases. Activated microglia secrete high levels of glutamate, which damages CNS cells and has been implicated as a major cause of neurodegeneration in these conditions. Glutamate-receptor blockers and microglia inhibitors (e.g. minocycline) have been examined as therapeutic candidates for several neurodegenerative diseases; however, these compounds exerted little therapeutic benefit because they either perturbed physiological glutamate signals or suppressed the actions of protective microglia. The ideal therapeutic approach would hamper the deleterious roles of activated microglia without diminishing their protective effects. We recently found that abnormally activated microglia secrete glutamate via gap-junction hemichannels on the cell surface. Moreover, administration of gap-junction inhibitors significantly suppressed excessive microglial glutamate release and improved disease symptoms in animal models of neurologic conditions such as stroke, multiple sclerosis, amyotrophic lateral sclerosis, and Alzheimer’s disease. Recent evidence also suggests that neuronal and glial communication via gap junctions amplifies neuroinflammation and neurodegeneration. Elucidation of the precise pathologic roles of gap junctions and hemichannels may lead to a novel therapeutic strategies that can slow and halt the progression of neurodegenerative diseases.